Maternal neurotic symptoms and infants' risk of developing persistent diarrhoea - Derek Humphreys; Magdalena Araya; Sylvia Cruchet; Julio Espinoza; Oscar Brunser (Universidade de São Paulo, 1996)
A previously calculated predictive model for health risk selects infants who suffer 4-5 times more morbidity than their unselected peers. Preliminary results suggested that this risk is related to maternal neurotic symptomatology. To evaluate this hypothesis, 52 consecutive mothers whose infants had a positive predictive score (Group 1) and 52 in whom this was negative (Group 2) were evaluated by means of Goldberg's General Health Questionnaire (GHQ - 30). A total of 41.9% and 20.5% of the mothers in Groups 1 and 2, respectively, scored above 11 points in GHQ-30, established as the cut off point. It is concluded that among poor urban families in Santiago mothers of infants with high risk of persistent diarrhoea have increased frequency of detectable neurotic symptoms. New programs aimed at this type of infant should include psychological support for their mothers.